Beyond microRNA – Novel RNAs derived from small non-coding RNA and their implication in cancer - Martens-Uzunova, Elena S.; Olvedy, Michael; Jenster, Guido (Cancer letters, 2013)
► SnoRNAs and tRNAs are specifically processed to different, functional types of smaller RNAs referred to as sdRNAs and tRFs. ► The expression of many snoRNAs, tRNAs, and derived from them smaller RNAs is altered in human disease and cancer. ► SdRNAs and tRFs share components of the molecular pathways of RNAi and may function in gene regulation or stress signaling. ► SnoRNAs, tRNAs, and derived from them smaller RNAs are potential oncogenes or tumor suppressor genes. ► SdRNAs and tRFs may provide new perspectives for the development of novel biomarkers and therapeutic strategies in cancer. Over the recent years, Next Generation Sequencing (NGS) technologies targeting the microRNA transcriptome revealed the existence of many different RNA fragments derived from small RNA species other than microRNA. Although initially discarded as RNA turnover artifacts, accumulating evidence suggests that RNA fragments derived from small nucleolar RNA (snoRNA) and transfer RNA (tRNA) are not just random degradation products but rather stable entities, which may have functional activity in the normal and malignant cell. This review summarizes new findings describing the detection and alterations in expression of snoRNA-derived (sdRNA) and tRNA-derived (tRF) RNAs. We focus on the possible interactions of sdRNAs and tRFs with the canonical microRNA pathways in the cell and present current hypotheses on the function of these RNAs.